If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(x-2)=1/2(2x-6)
We move all terms to the left:
-4(x-2)-(1/2(2x-6))=0
Domain of the equation: 2(2x-6))!=0We multiply parentheses
x∈R
-4x-(1/2(2x-6))+8=0
We multiply all the terms by the denominator
-4x*2(2x-6))-(1+8*2(2x-6))=0
Wy multiply elements
-8x^2(2+16x(2=0
| 290=80d | | 13x+9=8x+24 | | 12v+2v=42 | | 3+2(x-4)=12 | | 14x+4=9x-46 | | 19-t=-27 | | 5v+6v=-88 | | 2m-5=-12 | | 11x+7=6x-43 | | 15x-7=5x+33 | | 85x-119=17(5x-7) | | 19x-5=9x-75 | | -13=5+h | | 11x-3=7x+21 | | 18x3+10=180 | | 512=5dd= | | 180=54(x+3) | | -2x+10x=-16 | | 14x+5=7x-30 | | 8x+12x-9=5(4x=10) | | 2^4x+1=8x+1 | | 15x-9=10x-34 | | 13x-3=5x-43 | | 13+6y=10 | | 3( | | 10x-6=3x-48 | | 7p+220=360 | | 15m+10=75 | | 3( | | 273=40x | | 9x+131=360 | | 3x-468+x/4=130 |